2021
DOI: 10.1111/ctr.14493
|View full text |Cite
|
Sign up to set email alerts
|

Decreased frequency of transplantation and lower post‐transplant survival free of re‐transplantation in LVAD patients with the new heart transplant allocation system

Abstract: Purpose:To evaluate the effect of the new heart transplant (HT) allocation system in left ventricular assist device (LVAD) supported patients listed as bridge to transplantation (BTT).Methods: Adult patients who were listed for HT between October 18, 2016 and October 17, 2019, and were supported with an LVAD, enrolled in the UNOS database were included in this study. Patients were classified in the old or new system if they were listed or transplanted before or after October 18, 2018, respectively.Results: A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Similarly, Nordan et al [22 ▪ ]. and Jani et al [23 ▪ ] in very similar analyses, reported the results of patients awaiting heart transplant with a durable LVAD from October 2015 to March 2020 and October 2016 to October 2019, respectively identified in the UNOS database. Both groups found that those listed under the new allocation system were less likely to die awaiting transplant or be removed from the waitlist compared to the old allocation system but that they were less likely to undergo heart transplantation.…”
Section: Impact Of the Changes To The Unos Donor Heart Allocation Systemmentioning
confidence: 84%
“…Similarly, Nordan et al [22 ▪ ]. and Jani et al [23 ▪ ] in very similar analyses, reported the results of patients awaiting heart transplant with a durable LVAD from October 2015 to March 2020 and October 2016 to October 2019, respectively identified in the UNOS database. Both groups found that those listed under the new allocation system were less likely to die awaiting transplant or be removed from the waitlist compared to the old allocation system but that they were less likely to undergo heart transplantation.…”
Section: Impact Of the Changes To The Unos Donor Heart Allocation Systemmentioning
confidence: 84%
“…These results support prior findings published early after the allocation system change which demonstrated that listing with IABP 10 and Impella 11 were not associated with posttransplant outcomes while durable LVAD at listing was associated with adverse posttransplant outcomes. 12–14 Given significant decline in the use of durable LVAD as a bridge to transplant, with patients eligible for LVAD potentially being bridged directly to transplant with tMCS—these results have important implications for evaluation of the current allocation system and for potential consideration of changes for future allocation systems. Particularly, as patients with the current generation of durable LVADs demonstrate improving intermediate term survival, 15 with patients without high-risk features demonstrating 2 years survival which is similar or better than transplant, 16 addition consideration for the role of durable LVAD within the allocation system will be needed to balance waitlist and posttransplant outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…While this has led to shorter time to transplantation for those acutely ill patients, it has led to fewer patients in the less urgent priority categories receiving a transplant. 33 , 34 A potential solution is to incentivize centers to expand donor selection criteria while reducing the risk of regulatory consequences for resultant outcomes, which may be marginally lower but would result in increased transplantation and ultimately longer survival in aggregate for patients waiting for transplantation.…”
Section: Discussionmentioning
confidence: 99%